ANALISIS STRATEGI PENGEMBANGAN PERBANKAN SYARIAH DI TADIKA BIJAK LESTARI AL-FIKH ORCHARD GEORGETOWN PENANG - Oktavianti, Reza; Amsari, Syahrul (Universitas Islam Negeri Sumatera Utara Medan, 2024)
This research aims to analyze the sharia banking development strategy at Tadika Bijak Lestari Al-Fikh Orchard Georgetown Penang, an Islamic educational institution in Malaysia. In the context of Islamic education, sharia banking is becoming increasingly important in educating the younger generation about Islamic values in financial management. Qualitative research methods were used, with data obtained through in-depth interviews with teaching staff, administrative staff and school leaders, as well as analysis of internal school documents. The research results identified a number of strategies that have been implemented by schools, including integrating sharia financial education in the curriculum, collaboration with sharia financial institutions, education for parents, providing information, and public awareness campaigns. Research also reveals supporting factors, such as commitment to Islamic education and public awareness, as well as inhibiting factors, such as a lack of initial understanding and limited resources. In conclusion, Tadika Bijak Lestari Al-Fikh Orchard has succeeded in becoming an agent of change in promoting sharia banking in its community, however challenges and opportunities still exist in further developing the sharia banking sector in Islamic education